2021
DOI: 10.3389/fphar.2021.731847
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy Summary for Cytokine Storm in COVID-19

Abstract: COVID-19 pneumonia caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has ravaged the world, resulting in an alarming number of infections and deaths, and the number continues to increase. The pathogenesis caused by the novel coronavirus was found to be a disruption of the pro-inflammatory/anti-inflammatory response. Due to the lack of effective treatments, different strategies and treatment methods are still being researched, with the use of vaccines to make the body immune becoming the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 103 publications
(99 reference statements)
0
10
0
Order By: Relevance
“…Clinical trials and cohort studies have also assessed the potential benefits of various other biologic therapies for the treatment of COVID-19 [ 91 , 92 ]. Immunotherapeutic approaches have aimed to improve patient outcomes through combatting the SARS-CoV-2-induced cytokine storm, with tocilizumab (targeting interleukin [IL]-6) and anakinra (targeting IL-1) among the biologics evaluated [ 91 ].…”
Section: Clinical Implications Of Sc Infliximab In the Covid-19 Pandemic Era And Beyondmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical trials and cohort studies have also assessed the potential benefits of various other biologic therapies for the treatment of COVID-19 [ 91 , 92 ]. Immunotherapeutic approaches have aimed to improve patient outcomes through combatting the SARS-CoV-2-induced cytokine storm, with tocilizumab (targeting interleukin [IL]-6) and anakinra (targeting IL-1) among the biologics evaluated [ 91 ].…”
Section: Clinical Implications Of Sc Infliximab In the Covid-19 Pandemic Era And Beyondmentioning
confidence: 99%
“…Clinical trials and cohort studies have also assessed the potential benefits of various other biologic therapies for the treatment of COVID-19 [ 91 , 92 ]. Immunotherapeutic approaches have aimed to improve patient outcomes through combatting the SARS-CoV-2-induced cytokine storm, with tocilizumab (targeting interleukin [IL]-6) and anakinra (targeting IL-1) among the biologics evaluated [ 91 ]. Janus kinase (JAK) inhibitors are another important class of agents demonstrating efficacy against COVID-19 [ 93 , 94 ]; however, a pooled analysis of data from registries for inflammatory arthritis, IBD, and psoriasis found that patients receiving JAK inhibitor monotherapy had higher odds of hospitalisation or death associated with COVID-19 than those receiving monotherapy with anti-TNF agents [ 95 ].…”
Section: Clinical Implications Of Sc Infliximab In the Covid-19 Pandemic Era And Beyondmentioning
confidence: 99%
“…Chronic obstructive pulmonary disease and smoking in patients with COVID-19 are associated with increased risk of severe disease and mortality [ 4 ], and comorbid ILD is a risk factor for poor outcomes in patients with COVID-19 [ 5 ]. IL-6 plays a critical role in the cytokine storm as it promotes helper T cell response but inhibits regulatory T cell function [ 1 , 2 ]; thus, tocilizumab, a recombinant anti-IL-6 monoclonal antibody, improves outcomes of patients with COVID-19 pneumonia and cytokine storm [ 6 ]. Baricitinib, an inhibitor of the JAK-signal transducer and activator of transcription pathway, affects the production of inflammatory cytokines that contribute to the cytokine storm, such as IL-1β, IL-6, tumor necrosis factor-α, and IL-8 [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection was first reported in December 2019; however, effective therapy for COVID-19-associated acute lung injury remains to be elucidated [ 1 ]. Tocilizumab, a humanized antihuman interleukin (IL)-6 receptor monoclonal antibody, is typically used to treat rheumatoid arthritis and cytokine release syndrome [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The primary issue is abnormal activation of different cell types and persistent pro-inflammatory cytokine production in severe cases of the disease, and these two factors usually converge, inducing critical disturbance on both local and systemic levels. For instance, ‘cytokine storm’, a widespread and massive release of pro-inflammatory cytokines and chemokines, induces extrapulmonary involvement and possibly fatal complications associated with multisystem inflammatory syndrome leading to alterations in differentiation, proliferation, and activation of various immune cells, as well as in the ‘polarization’ of CD4+ and CD8+ T cells [ 7 , 8 ]. Furthermore, high plasma concentrations of extracellular vesicles, originating from the cytoplasmic membrane budding in activated platelets and endothelial cells [ 9 ], leukocytes and neutrophils [ 10 ], or even virus-specific T and B cell subsets [ 11 ], contribute to the pathological inflammatory response during the acute COVID-19.…”
Section: Introductionmentioning
confidence: 99%